Epidemiologic Investigation of Injuries Associated With the 2013 Fertilizer Plant Explosion in West, Texas. (2nd March 2016) - Metzger, Kristi; Akram, Hammad; Feldt, Bonnie; Stone, Kahler; Alvey, Stephanie; Henley, Sandi; Hernandez, Alicia; Melville, Sharon; Haywood, Tracy; Zane, David
Abstract: Objective: On April 17, 2013, a fire and subsequent explosion occurred at the West Fertilizer Company plant in West, Texas, and caused extensive damage to the adjacent neighborhood. This investigation described the fatal and nonfatal injuries caused by the explosion. Methods: Persons injured by the fertilizer plant explosion were identified through death certificates, medical examination reports, medical records, and survivor interviews. Data on patient characteristics, type of injury, and location of injury were collected. Results: Medical record review indicated that 252 individuals sought medical care for nonfatal injuries directly related to the explosion immediately after the explosion. Fifteen patients died of injuries sustained by the blast. Almost one-quarter of patients were admitted for treatment of injuries. Injuries sustained in the explosion included abrasions/contusions, lacerations/penetrating trauma, traumatic brain injuries/concussions, tinnitus/hearing problems, eye injuries, and inhalational injuries. Patients located closer to the explosion were more likely to be admitted to the hospital for treatment of injuries than were those who were located further away. Conclusion: Explosions of this magnitude are rare, but can inflict severe damage to a community and its residents. This investigation could be a useful planning resource for other communities, public health agencies, first responders, and medical facilities. ( Disaster Med Public Health Preparedness . 2016;10:583–590)